The fluidity of inventor networks - Michael Fritsch; Moritz Zöllner (Friedrich Schiller University Jena, 2017)
We investigate the stability of cooperative relationships between inventors and consequences for the characteristics and patent productivity of the respective regional innovation systems (RIS). The empirical analysis is for nine German regions over a period of 15 years. We find a rather high level of "fluidity", i.e., entry and exit of actors, as well as instability of their relationships over time. The aggregate characteristics of the regional networks are, however, quite robust even with high levels of micro-level fluidity. There are both significantly positive and negative relationships between micro-level fluidity and the performance of the respective RIS.
Keywords: O3; R1; D2; D8; 330; division of innovative labor; Innovation networks; patents; R&D cooperation